2018
DOI: 10.1016/j.rmed.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment perceptions in patients with asthma: Synthesis of factors influencing adherence

Abstract: Background: Non-adherence to asthma treatment is a contributing factor for poorly controlled asthma. Aim: The aim of this systematic review is to explore patients' perceptions of their inhaled asthma treatment, and how these relate to adherence, using both qualitative and quantitative data. Methods: Pre-determined search terms and inclusion criteria were used to search electronic databases (The Cochrane Library, MEDLINE, EMBASE and PsycINFO). Two researchers screened titles and abstracts using the Rayyan web a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 83 publications
(251 reference statements)
3
32
0
1
Order By: Relevance
“…For example, patients may have low expectations of what treatment can achieve, 19 have concerns about taking inhalers and use of inhaled corticosteroids or believe they are only needed intermittently. 20 21 In addition, there is evidence that patients would prefer to take a combined preventer and reliever inhaler in response to symptoms over a daily preventer inhaler with a reliever inhaler for symptom relief. 22 …”
Section: Introductionmentioning
confidence: 99%
“…For example, patients may have low expectations of what treatment can achieve, 19 have concerns about taking inhalers and use of inhaled corticosteroids or believe they are only needed intermittently. 20 21 In addition, there is evidence that patients would prefer to take a combined preventer and reliever inhaler in response to symptoms over a daily preventer inhaler with a reliever inhaler for symptom relief. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Adherence to medication is complex and affected by multiple factors (10)(11)(12). Non-adherence is caused by a combination of unintentional (related to practical barriers) and intentional (related to motivation and beliefs) barriers to take medication (5).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a review on adherence in autoimmune conditions also concluded that economic, demographic, and clinical characteristics were only moderately linked to adherence or persistence (21). The ndings on the prospective association of beliefs about medication with adherence and persistence in medication taking is congruent with previous work in other conditions (37)(38)(39). Still, beliefs about medication were scarcely studied among PwMS; the only study that examined adherence to DMTs was cross-sectional and found no association between medication beliefs and adherence (13).…”
Section: Discussionmentioning
confidence: 57%